Signature of a sudden stratospheric warming in the near-ground 7Be flux. (July 2015) - Pacini, A.A.; Usoskin, I.G.; Mursula, K.; Echer, E.; Evangelista, H.
Abstract: We present here an evidence that cosmogenic 7 Be isotopes produced in the lower stratosphere were measured in near-ground air at Rio de Janeiro, Brazil, after the southern hemispheric Sudden Stratospheric Warming (SSW) of 2002. The analysis presented here is based on a comparison of 7 Be data measured around Angra Nuclear Power Station (23°S 44°W) during the last three decades and a model estimate of the near-ground air 7 Be concentration using the CRAC: 7 Be model of cosmogenic production together with a simplified model for atmospheric 7 Be deposition that assimilates the regional precipitation data. Our results indicate that an anomalous stratosphere–troposphere coupling associated to the unique SSW of 2002 allowed stratospheric aerosols carrying 7 Be to reach the ground level very quickly. This methodology points to an important use of 7 Be as a quantitative tracer for stratospheric influence on near-ground air patterns. Highlights: We present a new improved model of 7 Be vertical transport in the lower atmosphere. The model reproduces the data from Brazil since 1986 except a spike in 2002–2003. The spike is explained as a signature of the southern hemisphere SSW of 2002. The result suggests that stratospheric aerosols can reach the ground in such events. It is discussed that near-ground air 7 Be can trace large-scale air mass dynamics.